Massive Open Online Courses (MOOCs) as Catalysts of Change in Education During Unprecedented Times: A Narrative Review - Rulinawaty Rulinawaty; Agus Priyanto; Setyo Kuncoro; Dwi Rahmawaty; Andi Wijaya (Jurnal Penelitian Pendidikan IPA, 2023)
This article delves into the significance of Massive Open Online Courses (MOOCs) in education, particularly during the COVID-19 pandemic. MOOCs, accessible to all at no cost, have emerged as a vital solution for remote learning challenges. They offer flexibility, accessibility, and adaptability, enabling uninterrupted learning from home. MOOCs hold several advantages. They empower self-directed learning by accommodating varying schedules. Interaction and collaboration thrive through discussion forums and shared projects, fostering social learning. Lifelong learning is promoted through continuous skill enhancement. Digital literacy is honed, vital in a digital world. MOOCs facilitate affordable distance learning without relocation. They grant access to prestigious universities and offer certificates for career advancement. While transformative, MOOCs can't fully replace traditional education due to challenges like limited direct interaction. They should complement existing systems. In Indonesia, MOOCs can improve education accessibility, especially in remote areas. Yet, equitable quality and widespread internet access remain crucial concerns.